2017
DOI: 10.1111/are.13411
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and amino acids metabolic response to heat stress in the intestine of the sea cucumberApostichopus japonicus

Abstract: The sea cucumber Apostichopus japonicus is an economic species mainly distributed along the coast of northern China, south‐eastern Russia, Japan, Republic of Korea and Democratic People's Republic of Korea. Aquaculture industry of A. japonicus has been facing severe challenge of high temperature. In this study, we studied the mRNA expression profiles of eight key metabolic enzymes involved in carbohydrate and amino acids metabolism in A. japonicus under heat stress. The expression of hexokinase, pyruvate kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 47 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Valine is a branched-chain AA; valine catabolism begins with the elimination of the amino group by transamination, giving alpha-ketoisovalerate, an alpha-keto acid, which is then transformed to isobutyryl-CoA through oxidative decarboxylation by the branched-chain α -ketoacid dehydrogenase complex [ 27 ]. Similar to the present study, Xu et al [ 28 ] observed that the valine concentration was increased in Apostichopus japonicus during short-term acute HS. We argue that valine is a potential marker for short-term HS.…”
Section: Discussionsupporting
confidence: 91%
“…Valine is a branched-chain AA; valine catabolism begins with the elimination of the amino group by transamination, giving alpha-ketoisovalerate, an alpha-keto acid, which is then transformed to isobutyryl-CoA through oxidative decarboxylation by the branched-chain α -ketoacid dehydrogenase complex [ 27 ]. Similar to the present study, Xu et al [ 28 ] observed that the valine concentration was increased in Apostichopus japonicus during short-term acute HS. We argue that valine is a potential marker for short-term HS.…”
Section: Discussionsupporting
confidence: 91%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ As reported in previous studies, abalones experienced elevated ammonia excretion rate and weight loss when reared under high temperature 11,24 , suggesting the increased contribution of protein/amino acid oxidation to their energy supply. The metabolomics-based studies on small abalone H. diversicolor 43 , sea cucumber Apostichopus japonicushas 38,44 also showed the influence of heat stress on amino acid metabolism. In this study, tissue concentrations of two tryptophan metabolic intermediates significantly increased after heat stress (Table 1): L-kynurenine and indole-3-lactic acid (3-IAA).…”
Section: Discussionmentioning
confidence: 94%
“…Acclimation in tanks lasted for 2 weeks. During both the acclimation and treatment experiment, the sea cucumbers were fed with regular fodder, and half of the water was changed daily [47].…”
Section: Methodsmentioning
confidence: 99%